2014
DOI: 10.1248/bpb.b14-00447
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel Class of Diacylglycerol Acyltransferase 2 Inhibitors with a 1<i>H</i>-Pyrrolo[2,3-<i>b</i>]pyridine Core

Abstract: Diacylglycerol acyltransferase 2 (DGAT2), which catalyzes the final step in triacylglycerol (TG) synthesis, is a key enzyme associated with hepatic steatosis and insulin resistance. Here, using an in vitro screen of 20000 molecules, we identified a class of compounds with a substituted 1H-pyrrolo[2,3-b]pyridine core which proved to be potent and selective inhibitors of human DGAT2. Of these compounds, H2-003 and -005 exhibited a considerable reduction in TG biosynthesis in HepG2 hepatic cells and 3T3-L1 preadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Inhibition of DGAT2 is being considered as a therapy for NAFLD/NASH in humans. (12,14,15) In this respect, our findings in mice suggest that DGAT2 inhibition could be effective in lowering hepatic fat content in humans and may do so without increased risk of inflammation and injury. Additionally, we found no adverse effects on insulin sensitivity with DGAT2 deletion in liver.…”
Section: Female Control Female Ldgat2komentioning
confidence: 72%
See 2 more Smart Citations
“…Inhibition of DGAT2 is being considered as a therapy for NAFLD/NASH in humans. (12,14,15) In this respect, our findings in mice suggest that DGAT2 inhibition could be effective in lowering hepatic fat content in humans and may do so without increased risk of inflammation and injury. Additionally, we found no adverse effects on insulin sensitivity with DGAT2 deletion in liver.…”
Section: Female Control Female Ldgat2komentioning
confidence: 72%
“…It is unclear whether blocking TG synthesis by DGAT2 would be beneficial for treating human NAFLD. This is an important question, given that highly potent and specific inhibitors are available for DGAT2 . To address this question, DGAT2 activity was previously lowered in adult mice by inhibiting enzymatic activity or gene expression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting TG synthesis has been proposed as a therapeutic strategy for hyperlipidemia for more than a decade 9 . Multiple small molecular inhibitors of DGAT, especially DGAT2, have been developed recently 18 , 27 , 28 . However, previous studies have suggested that inhibition of TG synthesis and turnover in the heart could contribute to lipotoxicity and hence cautioned the use of pharmacological inhibition of DGAT.…”
Section: Discussionmentioning
confidence: 99%
“…13 However, the assay conditions reported produced a small window (~1.5-fold) for DGAT2 compared with mock membranes. Recently, new in vitro approaches have been developed for DGAT2 screening assays, including the use of basic FlashPlate, which is based on scintillation proximity assay, 14,15 and mass spectrometry (HTMS). 16 Here we describe additional attempts to generate a robust DGAT2 assay amenable to small-molecule screening and detailed enzymatic characterization for development of highly potent DGAT2 inhibitors.…”
Section: Introductionmentioning
confidence: 99%